The Filth of Progress: Immigrants, Americans, and the Building of Canals and Railroads in the West - Hall, Greg (Labour / Le Travail, 2017)
This article reviews the book, "The Filth of Progress: Immigrants, Americans, and the Building of Canals and Railroads in the West," by Ryan Dearinger.